Exercise-induced muscle injury: delayed onset muscle soreness - Bisciotti, G. N.; Eirale, C. (Medicina dello Sport, 2012)
The intense exercise, especially when based on the eccentric contraction causes, as is well known, micro-lesions in the muscle structure which results in a metabolic and mechanical framework known with the name of DOMS, that is the acronym of Delayed Onset Muscle Soreness. Despite the first description of DOMS goes back to early last century, some of its aspects are not yet fully understood and some points haven't, just today, scientific evidence. However, much is known, mainly on the muscle ultrastructural changes that results from DOMS. There are also several studies focused on blood markers of exercise-induced muscle damage. The pathology associated with DOMS is often subclinical and the symptoms can be very variable also if, in general manner, we can say that the loss of strength reached its peak in the first 48 hours after the exercise induced muscle damage with a full recovery after 5 days and the peak of pain and weakness are reached after 1-3 days and usually cease after about 7 days. The DOMS can adversely affects the athletic performance altering both muscle function and joint mechanical. In addition, it is important to emphasize that the DOMS phenomenon can potentially be an important risk factor for muscle injury. Literature is somewhat equivocal concerning the drug therapy, the supplementation, the care and the DOMS prevention. The only evidence that we can find in the literature regarding the DOMS preventive aspect are related to the method called "repeated-bout effect", on the contrary many other aspects, both curative and preventive, still require further research to substantiate their evidence.